The impact of psychostimulants on central and peripheral neuro-immune regulation: a scoping review of cytokine profiles and their implications for addiction - Bravo, Joana; Magalhães, Catarina; Andrade, Elva B.; Magalhães, Ana; Summavielle, Teresa (Frontiers in Cellular Neuroscience, 2023)
It is now well accepted that psychostimulants act on glial cells causing neuroinflammation and adding to the neurotoxic effects of such substances. Neuroinflammation can be described as an inflammatory response, within the CNS, mediated through several cytokines, reactive oxygen species, chemokines and other inflammatory markers. These inflammatory players, in particular cytokines, play important roles. Several studies have demonstrated that psychostimulants impact on cytokine production and release, both centrally and at the peripheral level. Nevertheless, the available data is often contradictory. Because understanding how these cytokines are modulated by psychoactive substances seems crucial to perspective successful therapeutic interventions, here, we conducted a scope review of the available literature. We have focused on how different psychostimulants impact on the cytokine profile. Publications were grouped according to the substance addressed (methamphetamine, cocaine, methylphenidate, MDMA or other amphetamines) and the type of exposure and period of evaluation (acute, short- or long-term exposure, withdrawal and reinstatement). Studies were further divided in those addressing central cytokines, circulating (peripheral) levels, or both. Our analysis showed that the classical pro-inflammatory cytokines TNF-ɑ, IL-6 and IL-1β were those more investigated. The majority of studies have reported increased levels of these cytokines in the central nervous system after acute or repeated drug. However, studies investigating cytokine levels during withdrawal or reinstatement have shown higher variability in their findings. Although we have identified fewer studies addressing circulating cytokines in drug use, the available data suggest that the results may be more robust in animal models than in patients with problematic drug use. As a major conclusion, an extensive use of arrays for relevant cytokines should be considered to better determine which cytokines, upon the classical ones, may be involved in the progression from episodic use to the development of addiction. A concerted effort is still necessary to address the link between peripheral and central immune players, including from a longitudinal perspective. Until there, the identification of new biomarkers and therapeutic targets to envision personalized immune-based therapeutics will continue to be unlikely.